2022
DOI: 10.3389/fevo.2022.765148
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization of Biocrust-Plant Spatial Configuration for Dry Ecosystem Restoration Using Water Redistribution and Erosion Models

Abstract: Land degradation is one of the main threats to dryland sustainability in the next decades, hence restoration of the degraded land from drylands is an urgent need to maintain ecosystem functionality and their ability to provide ecosystem services. To achieve this goal, restoration practices should pursue the recovery of the main ground components, arranged in an optimal spatial configuration, to mimic undisturbed natural conditions. Drylands function as complex ecohydrologically coupled systems in which interpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…Currently large parts of dry forests are threatened by desertification caused by unsustainable anthropogenic land exploitation ( Miles et al, 2006 ; Vieira et al, 2015 ). However, biocrusts have been proven to be useful tools for nature-based dryland restoration and to combat land degradation and desertification ( Dadzie et al, 2022 ; Maggioli et al, 2022 ). Their influence could become even more important, since dry forests will face dramatic changes and climate extremes, particularly an increase in drought stress for vascular plants ( Torres et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently large parts of dry forests are threatened by desertification caused by unsustainable anthropogenic land exploitation ( Miles et al, 2006 ; Vieira et al, 2015 ). However, biocrusts have been proven to be useful tools for nature-based dryland restoration and to combat land degradation and desertification ( Dadzie et al, 2022 ; Maggioli et al, 2022 ). Their influence could become even more important, since dry forests will face dramatic changes and climate extremes, particularly an increase in drought stress for vascular plants ( Torres et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al [ 10 ] designed a runoff field on a highway slope with the optimum plant community combination identified through experimental data. Scholars have also suggested that plant communities should be configured to include trees, shrubs, and grasses that are drought- and cold-resistant and thus show high environmental adaptability [ 11 ]. Research has also revealed that combining legumes with perennial herbs benefits slope reclamation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, restoration strategies using plants and biocrusts have mostly developed as independent basic and applied research areas. However, integration of these restoration disciplines, by practices including plant and biocrust co‐introduction, maybe a more efficient means for initializing ecosystem structural and functional restoration (Maggioli et al 2022). In addition, the value of plant/biocrust interactions has recently been identified as an essential topic worthy of further study to improve ecosystem restoration, given the positive effects of one on the other (Antoninka et al 2021; Bowker et al 2022).…”
Section: Introductionmentioning
confidence: 99%